Risk factors and predictors of psoriatic arthritis in patients with psoriasis Fatores de risco e preditivos do desenvolvimento de artrite psoriásica em pacientes portadores de psoríase - Valderilio Feijó Azevedo; Pedro Grachinski Buiar (Sociedade Brasileira de Dermatologia, 2013)
Given the potential consequences of joint damage for patients with psoriatic arthritis, we believe that the optimization of screening methods and the investigation of arthritis in patients with psoriasis are a medical priority. It is very useful to identify predictors of arthritis in patients with psoriasis. In fact, there is a consensus among doctors that the large gap between the diagnosis of psoriasis and that of psoriatic arthritis should be narrowed. In order to better manage patients with psoriasis, the authors review and discuss recent publications on the evidence of current predictors of arthritis in patients with psoriasis. Em virtude das potenciais sequelas envolvidas no dano articular da artrite psoriásica, configura-se em uma prioridade médica a otimização dos métodos de rastreio e investigação de artrite nos pacientes com psoríase. Identificar preditores de artrite em pacientes com psoriase é fundamental para a prática clinica, além disso há um reconhecimento de que o grande intervalo entre o diagnóstico de psoríase e o diagnóstico de Artrite psoriásica em sua fase inicial deve ser reduzido. No sentido de contribuir com uma melhor abordagem de pacientes com psoríase, os autores revisam e discutem recentes publicações com evidencias de alguns fatores preditores de inicio de artrite nestes pacientes.